The prevalence of dental anxiety and fear in patients referred to Isfahan Dental School, Iran - Saatchi, Masoud (Dent Res J (Isfahan), 2015)
BACKGROUND: Dental anxiety and fear are major complications for both patient and dental care provider. The purpose of this study was to assess the prevalence of dental anxiety and fear in patients who referred to Isfahan Dental School and their relation to their age, gender, educational level, past traumatic experiences and frequency of dental visits. MATERIALS AND METHODS: In this cross-sectional study, 473 patients were provided with a questionnaire including three sections. First section contained questions concerning their age, gender, educational level, frequency of dental visits, reasons for irregular attendance and existence of past traumatic experiences. Second section comprised a Farsi version of Modified Dental Anxiety Scale (MDAS); and third included a Farsi version of dental fear survey (DFS). Data were analyzed by t-test, ANOVA, Pearson and Spearman correlation tests. RESULTS: The prevalence of dental anxiety among the study population was 58.8%. No correlation was found between age and MDAS (r = −0.08, P = 0.07) and DFS (r = −0.03, P = 0.53). Women demonstrated higher anxiety (P < 0.001) and fear (P = 0.003). Education had no significant effect on dental anxiety (r = −0.046, P = 0.32) and dental fear (r = −0.017, P = 0.79). Previous traumatic experiences were found to result in elevated anxiety and fear (P < 0.001). There was an inverse relationship between frequency of dental attendance and anxiety (r = −0.128, P = 0.008). CONCLUSIONS: Within the limitations of this study, anxiety associated with dental treatment was widespread in the study population. Dental fear and anxiety were not affected by age or education level. Dental fear and anxiety were higher in women. In addition, people who visited the dentist more regularly and individuals without previous traumatic dental experiences were less anxious.